Splicing to Keep Cycling: The Importance of Pre-mRNA Splicing during the Cell Cycle. Issue 3 (March 2021) - Petasny, Mayra; Bentata, Mercedes; Pawellek, Andrea; Baker, Mai; Kay, Gillian; Salton, Maayan
Abstract : Pre-mRNA splicing is a fundamental process in mammalian gene expression, and alternative splicing plays an extensive role in generating protein diversity. Because the majority of genes undergo pre-mRNA splicing, most cellular processes depend on proper spliceosome function. We focus on the cell cycle and describe its dependence on pre-mRNA splicing and accurate alternative splicing. We outline the key cell-cycle factors and their known alternative splicing isoforms. We discuss different levels of pre-mRNA splicing regulation such as post-translational modifications and changes in the expression of splicing factors. We describe the effect of chromatin dynamics on pre-mRNA splicing during the cell cycle. In addition, we focus on spliceosome component SF3B1, which is mutated in many types of cancer, and describe the link between SF3B1 and its inhibitors and the cell cycle. Highlights: Pre-mRNA splicing is a crucial process that allows proper progression of the cell cycle. Thus, inhibiting the spliceosome or silencing a specific splicing factor often promotes cell-cycle arrest. Splicing factors are regulated by transcription and post-translational modifications to alter their function to fit the specific requirement of each cell-cycle phase. Splicing factor function is changed by regulating their protein–protein and protein–RNA interactions, intracellular localization, trafficking, and activation. Chromatin is emerging as a novel key regulator of alternative splicing. Chromatin dynamics during the cell cycle can potentially promote a specific splicing pattern to allow cell-cycle progression.